Tensile strain hardening of a metakaolin based fibre reinforced composite - Ferreira, Bárbara Daniela da Costa (2016)
Portland cement concrete is the most used building material in the world. However, its manufacture is energy-intensive and it is susceptible to harsh environments. Alternative binder systems without ordinary Portland cement, such as geopolymers or alkali-activated materials, are recently new in the Civil Engineered world. These alternative binder systems seek, among other characteristics, improved durability and environmental efficiency. The attaining of strain hardening and multiple cracking typical of Strain Hardening Cementitious Composites (SHCC) using these alternative binder systems is very attractive from a conceptual point of view, since additional endurance to certain harsh or extreme environments, as well as enhanced durability, are usually expected as two of the main outcomes. In the present work, the behaviour of two different composites was studied: an existing Engineered Cementitious Composite (ECC) and a new composite based on an alternative binder prepared with metakaolin. Polyvinyl alcohol (PVA) fibres were used in both materials. A series of experiments, including compressive and direct tensile testing were carried out to characterize and compare the mechanical properties of both materials. The results showed that the alternative binder composite, when subjected to uniaxial tension, developed multiple cracks at steadily increasing tensile stress and strain, which is also typical of ECCs showing strain hardening behaviour. The development of fibre reinforced geopolymer or alkali-activated materials showing strain hardening ability in tension may still be considered as a novel research topic, with great potential for creating new and interesting developments for Civil Engineering and structural applications, particularly the ones subjected to harsh environments.